Population‐specific migratory strategies of Twite Linaria flavirostris in Western Europe. (25th December 2019) - Dunning, Jamie; Finch, Tom; Davison, Angus; Durrant, Kate L.
Abstract : Migratory connectivity describes the extent to which different individuals from specific breeding populations use similar non‐breeding sites, with important consequences for the demography and population structure of birds. We used mark‐recapture data from the EUring data bank to describe the non‐breeding range of Twite Linaria flavirostris within Western Europe. We quantified the strength of migratory connectivity across all European breeding populations, and for the British and continental breeding populations separately. Twite from different parts of the British breeding range used different non‐breeding areas from one another, whereas Twite from different parts of the continental breeding range used similar non‐breeding areas. There was essentially no overlap during the non‐breeding season between British and continental Twite.